Correction: Honegger et al. Antimicrobial Efficacy of Five Wound Irrigation Solutions in the Biofilm Microenvironment In Vitro and Ex Vivo. Antibiotics 2025, 14, 25 - Anja L. Honegger; Tiziano A. Schweizer; Yvonne Achermann; Philipp P. Bosshard (Antibiotics, 2025)
There was an error in the original publication [...]